DOCUMENT SERVING THE CONCLUSION OF A CONTRACT AND CONVEYANCE OF A RIGHT: INTERWEAVING OF THE ROMAN AND GREEK LEGAL TRADITIONS IN BYZANTINE PRIVATE LAW - Ilić, Tamara (Pravni zapisi, 2022)
The purchase contract, often referred to as sale and purchase (πρᾶσις καὶ ἀγορασία) as an illustration of its twofold nature derived from the Roman legal tradition, or simply as sale (πρᾶσις), is suitable for analyzing different legal issues. In light of typical Byzantine document named πρατήριον ἔγγραφον, we aim to define the nature of purchase contract in this medieval legal system. Diplomatic formulae contain data about consensus of contractual parties, as well as the fact that a document was drafted “for security”, which raises the question of solemnity of this contract. The role the deed has is also discussed in the paper, as in some cases it is uncertain whether the composition and delivery of the document also implied the passing of title. Applied methodological approach takes into account the linguistic interpretation of documentary clauses and legal provisions in codes, and relies on comparative-historical method.